Presidential Address: Ramsay Cook and the Writing of Canadian History, or What Can Ramsay Cook Still Teach Us? - Wright, Donald (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
Ramsay Cook (1931–2016) rewrote Canadian history. Distinctly uncomfortable with nationalism, like his intellectual hero George Orwell, he insisted on pluralism. His best-known contribution to Canadian historical writing was the idea of limited identities, which he refined across the length of his career but never abandoned. He also embraced federalism, bilingualism, multiculturalism, and minority rights as the best guarantees of difference. Herein lies the distilled essence of Ramsay Cook the historian.